Atala, Atala Hairstreak, Coontie Hairstreak, Eumaeus atala Röber (Insecta: Lepidoptera: Lycaenidae) - Donald W. Hall; Jerry F. Butler (EDIS, 2004)
The atala is our largest and most spectacular eastern U.S. hairstreak. Due to decline in abundance of its host plant, coontie, because of over-harvest (as a source of starch) and habitat destruction due to development, the atala was believed to have become extinct. It was not collected in Florida from 1937 until 1959. The atala is now common locally in southeast Florida probably as a result of the popularity of its host plant as a landscape ornamental. In fact, it is now occasionally considered a pest in ornamental plant nurseries. This document is EENY-169, one of the Featured Creatures series of the Entomology and Nematology Department, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2000.